'To give is better than to receive?' Couples massage significantly benefits both partners' wellbeing. (September 2020) - Naruse, Sayuri M; Cornelissen, Piers L; Moss, Mark
This experimental study evaluated the differential effects of 'giving' and 'receiving' massage on wellbeing in healthy but stressed couples. Forty-two volunteers started the study and of these, 38 (i.e. 19 couples) completed a 3-week massage course. Emotional stress and mental clarity were assessed before and after mutual massage between each pair of adults belonging to a couple at home. While massage benefitted both parties' wellbeing within a session, critically we found no differences in wellbeing between those 'giving' and 'receiving' massage. These novel findings suggest that home-based massage may be advocated to couples as a 'selves-care', health-promoting behaviour.